Digitally-induced change in the public sector : a systematic review and research agenda - Haug, Nathalie; Dan, Sorin; Mergel, Ines (Taylor & Francis, 2023)
Digital transformation has become a buzzword that is permeating multiple fields, including public administration and management. However, it is unclear what is transformational and how incremental and transformational change processes are linked. Using the PRISMA method, we conduct a systematic literature review to structure this growing body of evidence. We identified 164 studies on digitally-induced change and provide evidence for their drivers, implementation processes, and outcomes. We derive a theoretical framework that shows which incremental changes happen in public administrations that are implementing digital technologies and what their cumulative, transformative effects are on society as a whole.
Keywords: Digital transformation; digital government; public sector change; systematic literature review; PRISMA; fi=Julkisjohtaminen|en=Public Management|